Population-based assessment of factors influencing antibiotic prescribing for adults with dengue infection in Taiwan - Chia-En Lien; Yiing-Jenq Chou; Yi-Jung Shen; Theodore Tsai; Nicole Huang (Public Library of Science (PLoS), 2022)
Background Antibiotic treatment for dengue is likely considerable and potentially avoidable but has not been well characterized. This study aimed to assess antibiotic prescribing for confirmed dengue cases in outpatient and inpatient settings and to identify associated patient, physician and contextual factors. Methods 57,301 adult dengue cases reported in Taiwan between 2008-2015 were analyzed. We assessed both outpatient and inpatient claims data of dengue patients from a week before to a week after their dengue infections were confirmed under Taiwan's National Health Insurance program. A multivariable logistic regression with generalized estimating equations was used to estimate the probability of antibiotic prescribing in dengue patients. Results Overall, 24.6% of dengue patients were prescribed an antibiotic during the 14 day-assessment period. Antibiotics were prescribed in 6.1% and 30.1% of outpatient visits and inpatient admissions, respectively. Antibiotic prescriptions were reduced by ~50% in epidemic years. Among inpatients, advanced age, females, and major comorbidities were risk factors for receipt of an antibiotic; antibiotics were used in 26.0% of inpatients after dengue was diagnosed. Significant differences in antibiotic prescribing practices were observed among physicians in outpatient settings but not in inpatient settings. Conclusions In addition to patient and physician demographic characteristics, contextual factors such as care setting and during epidemics significantly influenced prescription of antibiotics. Characterization of prescribing patterns should help direct programs to curb antibiotic prescribing. Author summary Antimicrobial resistance is a growing global public health threat. The non-specific clinical manifestations of dengue overlap with signs and symptoms of other febrile illnesses common to tropical and subtropical zones making differential diagnosis between dengue and bacterial infections difficult, hence, leading to potentially unnecessary antibiotic prescribing. However, our understanding of factors underlying antibiotic prescribing for dengue is rather limited. Taiwan has experienced periodic dengue outbreaks and has a comprehensive national health insurance database including reliable infectious diseases surveillance and prescribing records. The findings in Taiwan show that other than commonly known patient characteristics, provider and contextual factors play a significant role. Physician's age and practice setting were significant factors influencing the decision to prescribe antibiotics, particularly in outpatient visits. The likelihood of prescribing an antibiotic to dengue patients was reduced by more than 50% in medical visits occurring after the dengue infection was confirmed. Understanding patient, provider and contextual factors in antibiotics prescription for dengue infections can provide insights for improved antibiotic stewardship and unnecessary antibiotic treatment for dengue.